Limited Interactions between Streptococcus Suis and Haemophilus Parasuis in In Vitro Co-Infection Studies - Mathieu-Denoncourt, Annabelle (Pathogens, 2018)
Streptococcus suis and Haemophilus parasuis are normal inhabitants of the porcine upper respiratory tract but are also among the most frequent causes of disease in weaned piglets worldwide, causing inflammatory diseases such as septicemia, meningitis and pneumonia. Using an in vitro model of infection with tracheal epithelial cells or primary alveolar macrophages (PAMs), it was possible to determine the interaction between S. suis serotype 2 and H. parasuis strains with different level of virulence. Within H. parasuis strains, the low-virulence F9 strain showed higher adhesion levels to respiratory epithelial cells and greater association levels to PAMs than the high-virulence Nagasaki strain. Accordingly, the low-virulence F9 strain induced, in general, higher levels of pro-inflammatory cytokines than the virulent Nagasaki strain from both cell types. In general, S. suis adhesion levels to respiratory epithelial cells were similar to H. parasuis Nagasaki strain. Yet, S. suis strains induced a significantly lower level of pro-inflammatory cytokine expression from epithelial cells and PAMs than those observed with both H. parasuis strains. Finally, this study has shown that, overall and under the conditions used in the present study, S. suis and H. parasuis have limited in vitro interactions between them and use probably different host receptors, regardless to their level of virulence.